The Evaluation Of “Bahasa Inggris Maritim Dan Perikanan Paket Keahlian: Teknika Kapal Penangkapan Ikan Kelas X” - Stellar Nube Mella (Institute of Research and Community Outreach - Petra Christian University, 2018)
The purpose of this present study is to identify the extent to which the ESP textbooks Bahasa Inggris Maritim dan Perikanan Paket Keahlian: Teknika Kapal Penangkapan Ikan Kelas X Semester I(BIMP I)and Bahasa Inggris Maritim dan Perikanan Paket Keahlian: Teknika Kapal Penangkapan Ikan Kelas X Semester II (BIMP II) comply with the criterions of ESP textbooks evaluation checklist proposed by Cunningsworth (1995), namely the7th, 8th, 9th, and 11thcriterions of the checklist. This study is a qualitative research in which the writer read both ESP textbooks BIMP I and BIMP II and used content analysis to analyze the textbooks. Through the evaluation of both the ESP textbooks BIMP Iand BIMP II, the writer discovered that out of the four criterions used, the ESP textbooks partially met the ninth and eleventh criteria which are; the usability of the ESP textbooks for individual study, and the availability of outcomes of learning activities relevant to student’s future professions/ occupations. This present study would hopefully make several noteworthy contributions to the quality improvement of both BIMP Iand BIMP II textbooks.